1996
DOI: 10.1007/bf02730929
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A in day care centre

Abstract: A focal outbreak of hepatitis was detected in a day-care centre for children centrally located in Pune. The source of infection was suspected to be an 11-year-old child who probably got the infection from his school. Seven out of 15 children from day-care centre developed clinical hepatitis. Two cases of secondary infection were identified among the family contacts of infected children. Sera from all the nine sick children were positive for anti-hepatitis A virus-IgM antibodies. A stool sample from a case of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…In India, both HAV and HEV infections are endemic, HAV being mainly a disease of paediatric populations whereas HEV mainly affects young adults [13]. Epidemics of hepatitis A have been rare [24,26], whereas a large number of HEV outbreaks are reported from different parts of the country [12,27–29]. The disease also occurs in sporadic form and represents a major cause of acute viral hepatitis among Indian adults [30].…”
Section: Introductionmentioning
confidence: 99%
“…In India, both HAV and HEV infections are endemic, HAV being mainly a disease of paediatric populations whereas HEV mainly affects young adults [13]. Epidemics of hepatitis A have been rare [24,26], whereas a large number of HEV outbreaks are reported from different parts of the country [12,27–29]. The disease also occurs in sporadic form and represents a major cause of acute viral hepatitis among Indian adults [30].…”
Section: Introductionmentioning
confidence: 99%
“…The predominantly circulating genotype in India is genotype III A 8 10 11 12 . However, a few studies have reported circulation of genotype IA in New Delhi and also co-circulation of genotypes IIIA and IB has been reported from a day care center in Pune, western India 13 14 15 . The molecular characterization of the infectious agents is important, as it provides the information about the circulating strains in a particular region, the invasion of new strains from different geographical areas and their role in the pathogenesis and severity of the disease.…”
mentioning
confidence: 99%
“…As discussed before, this is a typical pattern of most childhood diseases (Galil et al, 2002), and hepatitis A as well (Chitambar et al, 1996).…”
mentioning
confidence: 53%
“…The aim of the considered social distancing measures is to interrupt the chains of cases observed in day care centers and kindergartens, which are typical of many childhood diseases (Galil et al, 2002), and viral hepatitis A as well (Chitambar et al, 1996). This is possible thanks to the explicit representation of the individuals and of the places where person-to-person transmission can occur.…”
Section: Social Distancingmentioning
confidence: 99%